Coarsening of martensite with multiple generations of twins in laser additively manufactured Ti6Al4V. (July 2021) - Pantawane, Mangesh V.; Sharma, Shashank; Sharma, Abhishek; Dasari, Sriswaroop; Banerjee, Srikumar; Banerjee, Rajarshi; Dahotre, Narendra B.
Graphical abstract: Abstract: Generation of inherently complex thermokinetics and thermomechanical conditions during the laser powder bed fusion-based additive manufacturing (LPBF-AM) process makes it challenging to understand the evolution of internally twinned martensite structure in Ti6Al4V. In view of this, the present study employed the finite element method based multiphysics thermokinetic and thermomechanical model in complement with experimental observations via scanning electron microscopy and transmission electron microscopy to study this occurrence. In order to understand the transient effects of thermokinetics and thermomechanics during multi-laser track treatment of LPBF-AM on evolution of the morphological features of martensite phase and twins, separate experiments involving laser surface melting with single, double, and triple laser tracks and conventional heat treatment (solutionized above β transus temperature of 1323 K followed by quenching in water at 298 K) of wrought Ti6Al4V were conducted. The major fraction of martensite laths were thinner in the water-quenched Ti6Al4V sample compared to LPBF-AM Ti6Al4V. The gradual coarsening and distortion of martensite lath seemed to occur with successive thermal cycles of single, double, and triple laser track treatments. In addition multiple generations of crystallographic twins were detected in LPBF-Ti6Al4V, which were rarely detected in solutionized and water quenched wrought Ti6Al4V. The multiple generations of twins were also distinct features of the single laser track treated wrought Ti6Al4V. The evolution of these morphologically and crystallographically diverse martensite phase structures were correlated with the computationally predicted thermokinetic and thermomechanical conditions during in-layer multi-laser track and multi-layer thermal treatments experienced during LBPF-AM process in the present study.